Ecological thresholds of hypoxia and sedimentary H2S in coastal soft-bottom habitats: A macroinvertebrate-based assessment. (May 2018) - Kanaya, Gen; Nakamura, Yasuo; Koizumi, Tomoyoshi
Abstract: Ecological thresholds of dissolved oxygen (DO) and sedimentary hydrogen sulfide (H2 S) for macrozoobenthos were examined during a 30-month monitoring of two stations in a highly eutrophic canal in inner Tokyo Bay, Japan. Bottom DO and H2 S concentrations fluctuated seasonally, and were significantly correlated with water and sediment temperatures. Red tide-derived phytodetritus was a major source of sediment organic matters in the canal bottom, and the sediment became highly reduced and sulfidic condition in warmer months (sedimentary H2 S; up to 8.5 mM). Dominant opportunistic taxa, including polychaetes and amphipods, were eliminated under low DO and high H2 S conditions (i.e., population thresholds), and devastation of community structure occurred at 2.4–3.3 mg l −1 DO and 1.8–2.7 mM H2 S (i.e., community thresholds). To maintain ecosystem function in anthropogenically degraded habitats and ensure colonization by macrozoobenthos throughout the year, DO and H2 S levels should be maintained below these thresholds. Highlights: Seasonal changes in infaunal community were asessed for 30-months in inner Tokyo Bay. Thresholds of DO and H2 S were examined both at population and community levels. Bottom DO and H2 S concentrations were clearly correlated with temperature. Rapid recovery of dominant opportunists occurred in winter as DO condition recovered. Infaunal community devastated at 2.4–3.3 mg l −1 DO and 1.8–2.7 mM H2 S.